2009
DOI: 10.1063/1.3088872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dielectric barrier discharges on silicon surfaces: Surface roughness, cleaning, and oxidation

Abstract: Silicon wafers were exposed to a dielectric barrier discharge (DBD) at atmospheric pressure, which was ignited by applying a high voltage (>12 kV peak voltage) to a small gap (d(g)=300 mu m) above the wafer surface in an oxygen process gas atmosphere. The effect of the DBD on H-terminated silicon and native silicon oxide surfaces was investigated in situ and ex situ by means of Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy (XPS). The influence of the treatment on surface roughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…The wafer temperature is not changed because of the short duration of the plasma discharges. Also, it has been reported that the wafer roughness is not modified by DBD plasma [34] after prolonged exposures, a result which is consistent with the observations made during this study as will be discussed in the next section.…”
Section: Plasma Activationsupporting
confidence: 93%
“…The wafer temperature is not changed because of the short duration of the plasma discharges. Also, it has been reported that the wafer roughness is not modified by DBD plasma [34] after prolonged exposures, a result which is consistent with the observations made during this study as will be discussed in the next section.…”
Section: Plasma Activationsupporting
confidence: 93%
“…Direct melanin layer deposition onto Si substrates has been achieved here by modifying the substrate surface wettability, i.e., by turning the not hydrophilic (almost hydrophobic) Si surface into a super hydrophilic one by a dry procedure. To this end, water‐vapor fed plasma produced by micro‐capillary dielectric barrier discharge (DBD) has been adopted as a dry procedure in an innovative fashion (see Supporting Information) 20. The Si surface wettability modification has been verified by the water contact angle (WCA) technique: a reduction from a WCA of 62° for the initial untreated surface to 3° (super‐hydrophilic) for the water‐plasma‐treated surface has been measured.…”
mentioning
confidence: 99%
“…Oxide thicknesses of 2.0 ± 0.2 nm and 3.2 ± 0.2 nm, respectively, were measured by X‐ray reflectometry (XRR). These samples were used to calibrate thickness measurement with X‐ray photoelectron spectroscopy (XPS) and ellipsometry 4…”
Section: Experimental Partmentioning
confidence: 99%
“…Unfortunately, it is attenuated by an oxide film of individual thickness. With the 6P‐method from Seah and Spencer, which we adapted to the special requirements of the DBD oxide, the oxide thickness can be determined very precisely from the Si2p spectrum 4. The thickness can then be used to calculate the nominal value of the elemental silicon peak for normalization purposes.…”
Section: Experimental Partmentioning
confidence: 99%